Efficacy of fractional co2 laser in the treatment of facial atrophic acne scars in Tishreen University Hospital outpatients in Lattakia 2017-2018 - Ismaiel, Mohamad; khaddam, Jamal; Issa, Ola (Latakia University Journal -Medical Sciences Series, 2020)
Background and objective: Facial scarring resulting from acne is a common cosmetic concern. Various modalities have been used to treat scars, but limited efficacy and problematic side effects have restricted their application .Fractional co2 laser is one of the modern methods of skin resurfacing , and this study aimed to assess the efficacy of this method in treating facial atrophic acne scars. Patients and methods: Thirty participants with facial atrophic acne scars, 17 female and 13 male, underwent to three treatment sessions with fractional co2 laser , at 4-6 week intervals. Treatment energy parameters were increased every session about 10 watt. Improvement of acne scarring was evaluated using ECCA Grading Scale before the first session and three months after the last session. We also evaluated resulting side effects after every session. Results: The mean ECCA score was 126.5 ± 30.6 before the first session and became 70.3 ± 27.5 three months after the last session . 86.6% and 33.3% of patients have got more than 25% and 50% improvement respectively. The best result was seen in boxcar type. Post inflammatory hyper pigmentation was the most frequent side effect . Conclusion: Fractional co2 laser is an effective and safe therapy for facial atrophic acne scars especially boxcar type. المقدمة : تعتبر الندب العدية أشيع اختلاطات العد الشائع ، وعلى الرغم من كثرة الوسائل المتاحة لعلاجها إلا أنه لا يوجد حتى الآن وسيلة تحقق الحل الأمثل . يعد ليزر co2 المجزأ من التقنيات الحديثة المستخدمة لتمليس الوجه وهدفنا في هذا البحث دراسة فعالية هذه التقنية في علاج الندبات العدية الضمورية التي تصيب الوجه . المواد وطرائق البحث: ضمت الدراسة 30 مريضاً (13ذكور – 17إناث) . خضعوا لثلاث جلسات علاجية بليزرco2 المجزأ بفاصل 4-6أسابيع بين الجلسات و باستخدام قيم طاقية متزايدة حوالي 10 واط كل جلسة. تمت دراسة درجة التحسن لدى كل مريض باستخدام مقياس ECCA قبل البدء بالعلاج وبعد ثلاثة أشهر من الجلسة الاخيرة . كما تم تقييم الآثار الجانبية الحاصلة بعد كل جلسة. النتائج: انخفضت قيمة متوسط مقياس ECCA بعد العلاج بمقدار 44.4% عن قيمته قبل العلاج .حقق 86,6% و 33,3% من المرضى درجات تحسن فوق 25% و 50% على التوالي . وُجدت أفضل النتائج في ندب صندوق السيارة . كان فرط التصبغ أشيع الآثار الجانبية وارتبط حدوثه بالتعرض للشمس . الخاتمة: ليزر co2 المجزأ وسيلة فعالة وآمنة لعلاج الندبات العدية الضمورية التي تصيب الوجه وبشكل خاص تلك المسماة ندب صندوق السيارة .